A QUALITATIVE STUDY INVESTIGATING HEALTHCARE PROFESSIONALS’ PERCEPTIONS OF COMMUNICATING WITH RELATIVES OF PATIENTS AT THE END OF LIFE - Shutt, Rebecca (2012)
The most common place of death in the early twenty-first century has become acute hospitals with less people experiencing End of Life (EOL) care in other settings such as at home or in residential care or hospice. End of Life care is an increasingly important sector of care within the UK, as life expectancy continues to rise and treatment methods that increase longevity will lead to a growing elderly population that will suffer from ageing diseases such as cancer and heart failure. Everyone is different so the impact death and dying has on relatives will vary also. Gaining a greater understanding of HCPs’ perceptions of communicating with relatives of those at the EOL will be insightful and allow for development of research. This can be achieved if research continues to seek further understanding of any challenging and recurrent situations experienced in an acute EOL care setting in the UK. A qualitative approach with semi-structured interviews was adopted to complete the research study. A purposive sample of six Health care Professionals, 3 Nursing Auxiliaries and 3 Staff Nurses participated. Interview questions asked about HCPs’ perceptions of communicating with relative of those at the end of life. This qualitative approach was used to investigate the views and experiences of HCPs in an acute EOL/Palliative care setting. Participants identified 4 key themes; Education, Learning through experience, confidence and competency and building rapport. All participants (SN) believed that education was not sufficiently covered in pre-registration training. Knowledge of EOL care and communication frameworks and policies yielded a varied response, some participants had no knowledge of policies and others regarded them as useful tools to assist communication at the EOL. Participants considered experiential learning the most significant factor influencing whether HCP’s felt confident communicating with relatives. The study shows HCP’s views on their ability to confidently communicate with relatives to be a multifactorial issue. Further research is recommended to further investigate the factors influencing HCP’s abilities to confidently communicate. This would improve current understanding of HCP’s views and experiences of communicating with relatives at the EOL and identify any further gaps in EOL care and communication training for HCP’s.